Structure and properties of in situ-generated two-dimensional turbostratic graphite nodules. (November 2017) - Binder, C.; Bendo, T.; Hammes, G.; Neves, G.O.; Binder, R.; de Mello, J.D.B.; Klein, A.N.
Abstract: Powder injection moulding and sintering were used to obtain iron-based self-lubricating composites in which SiC particles were used as precursors to generate graphite nodules dispersed in the composite matrix. Using thermodynamic simulations with DICTRA ®, it was possible to predict the SiC dissociation in the ferrous matrix studied (Fe+0.6C). The evolution of the dissociation of SiC particles during sintering was investigated by X-ray diffraction (XRD) and dilatometric analysis, whereas the structure and morphology of the graphite nodules were studied by field emission gun-scanning electron microscopy (FEG-SEM), micro-Raman spectroscopy, and transmission electron microscopy (TEM). To compare the characteristics of the graphite nodules, micro-Raman and tribological analyses (friction coefficient and wear rate) were carried out for nodular cast iron and graphite powder. Reductions in the friction coefficient and wear rate of the tribological pair can be associated with the turbostratic characteristics of the graphite nodules. Graphical abstract: